2021
DOI: 10.37742/jpoe.v3i2.131
|View full text |Cite
|
Sign up to set email alerts
|

Survey Kesadaran Masyarakat dalam Meningkatkan Kesehatan Fisik di Masa Pandemi

Abstract: Pandemi Covid 19 pada tahun 2020 membawa banyak perubahan dalam kehidupan masyarakat, semua hal harus dilakukan di rumah, belajar berkerja, beribadah bahkan berolahraga di lakukan dirumah. Rumusan masalah penelitian ini tentang Kesadaran masyarakat dalam mneingkatkan kesehatan dimasa pandemi, apabila kesadaran masyarakat dalam menjaga kesehatan meningkat maka akan menciptakan pola hidup sehat bagi tubuh dan lingkungan nya bahkan besar kemungkinan akan terhindar dari virus yang dapay membahayakan bagi tubuh. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…4 In another study in 2020. 24 it was found that 46.4% of the elderly population had a poor self-assessment of their health. This could be attributed to the fact that self-assessment of health was heavily influenced by the respondents' age, as they belong to the elderly age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In another study in 2020. 24 it was found that 46.4% of the elderly population had a poor self-assessment of their health. This could be attributed to the fact that self-assessment of health was heavily influenced by the respondents' age, as they belong to the elderly age group.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy habits such as consuming nutritious food, engaging in regular exercise, and getting sufficient rest appeared to have increased during the COVID-19 pandemic. 24 The statement can obtain appropriate assistance (P4). As many as 96.3% (443) of the respondents stated that they strongly agreed and agreed that it was easy to get help.…”
Section: Discussionmentioning
confidence: 99%
“…Kontribusi program ini meningkatkan kebutuhan layanan kesehatan meningkat 1,06% di tahun 2022 [1]. Kesadaran masyarakat mengkonsumsi makanan alami mampu meningkatkan kesehatannya 78,8% [2]. Makanan alami terutama mengandung vitamin, mineral, protein, dan sehat untuk menciptakan sistem kekebalan tubuh [3].…”
Section: Pendahuluanunclassified
“…During the COVID-19 pandemic, businesses in the health sector including the pharmaceutical industry became the favorites. The COVID-19 pandemic has affected the level of public awareness of health by 78.8% (Hardi et al, 2021). This is an opportunity for the pharmaceutical industry to grow faster by exploiting this opportunity.…”
Section: Introductionmentioning
confidence: 99%